Developing mental toughness: Lessons from Paralympians - Powell, A.; Myers, T. (Frontiers in Psychology, 2017)
Mental toughness (MT) is a key psychological variable related to perseverance and success in performance domains. MT and its development has been explored across a range of contexts and across different sports, but no research to date has examined MT in relation to Paralympic athletes. We sought to understand the lived-experiences of mentally tough Paralympians, aiming to conceptualize MT in a Paralympic context and investigate its development. Ten Paralympic athletes were interviewed using in-depth, semi-structured interviews. The verbatim transcripts of the interviews served as the data for an interpretative phenomenological analysis. Three broad themes and several subthemes emerged in conceptualizing Paralympian MT: characteristics (determination, defiance, pragmatic, optimistic, resilient, self-belief and independence and autonomy), cognitions (normalization, sense of escape, non-acceptance of constraints, influence perception and connection) and cognitive strategies (rational thinking, goal setting, pain management and control). In understanding MT development, two broad themes and several subthemes emerged: formative experiences (challenge, classification, setbacks, critical incident, trauma and recovery, sustained commitment, development of mind-set and perspective during challenge, failure, and acceptance), and support and coping resources (social support and significant others, external shaping, social support, overcoming problems, social comparison and reflective practice). The findings suggest that Paralympians benefited from exposure to highly demanding situations in a supportive environment and this helped develop mentally tough characteristics and behaviors and individualized cognitive coping strategies. Our findings highlight the association between the adaptive development of personal characteristics by overcoming physical and mental setbacks over a sustained time period. Overall, the findings suggest that to develop mentally tough characteristics and behaviors, athletes in general could benefit from exposure to highly demanding situations in a supportive environment.